Multifunctional plants used in the diet of Quilombolas in the Castainho Community (Garanhuns, Pernambuco). - Prada de la Cruz, Marleny; Trajano Nunes, Alissandra; Morais Oliveira, Antônio Fernando; de Holanda Cavalcanti , Laise (Ethnobotany Research and Applications, 2022)
Background: The rich flora of Brazilian biomes includes a potentially high amount of species capable of both nourishing and helping to prevent or treat diseases whose potential is still little explored. This study aims to provide information about the knowledge richness of multifunctional plants among quilombolas, generating information that can be used to improve the quality of life in the rural community of Castainho (Garanhuns, Pernambuco). Methods: Semi-structured interviews were conducted, associated with guided tours to collect the cited plants. The data obtained were analyzed using the Use value index (UV) for the species and Knowledge richness index (KRI) for the informants. Results: A total of 52 botany families, 117 genera, and 136 species were catalogued. Most species 47% (64) were used as medicine only, 21% (29) as food only, and 32% (43) were multifunctional plants, the latter being 12 natives to Brazil, 11 naturalized, and 20 exotic cultivated plants whose medicinal and nutritional properties were perceived by the interviewees. The inclusion of species native to Brazil, naturalized species, and exotic, but non-African species in the diet and medicinal flora of the quilombolas of Castainho attests to the cultural and environmental adaptations through which they have gone to survive and diversify their traditions. Keywords: Ethnobotany; African descendants; Medicinal plants; Food plants; Rural communities; Maroons.